Performance Assessment of the Internal Data Monitoring Information System (E-Simdatin) at the Directorate General of Regional Development - Bagus Eko Prasetyo; Marja Sinurat; baharudin Tahir (Sean Institute, 2024)
The e-Simdatin application is an important instrument in accelerating access to information, simplifying the data collection process, facilitating analysis and decision making related to regional development. This research aims to describe, analyze and determine the Performance Assessment at the Directorate General of Regional Development through the Internal Data Monitoring Information System (e-Simdatin) including supporting and inhibiting factors as well as efforts in implementing activities. The research method used was descriptive qualitative research using 9 informants determined by purposive sampling. The theory used in this research uses Mahsun's (2016) theory which consists of 6 dimensions and 10 indicators. Data collection uses interviews, observation, documentation and triangulation techniques. Based on data analysis and discussion regarding the Performance Assessment of the Internal Data Monitoring Information System (e-Simdatin) at the Directorate General of Regional Development, it is in accordance with the process, output, benefits, input, impact indicators. The results (outcomes) are good at 94.14, the results of the Budget Implementation Performance Indicator (IKPA) value by the Ministry of Finance and the Review Result Notes (CHR) of the Performance Report from the Inspectorate General of the Ministry of Home Affairs, achieving predetermined targets and increasing budget realization and performance. However, it still needs to be improved due to a shortage of Human Resources (HR) to support the implementation of the e-Simdatin application. Inhibiting factors are changes to indicator targets that are not immediately changed, input at the end of the deadline, low competence, lack of PIC concern, and no satisfaction rating available on the e-Simdatin application. Supporting factors are the availability of SOPs, guidebooks, IT equipment, and leadership support. Efforts that should be made include changing targets on time, clarity in inputting output, socializing the use of the e-Simdatin application, fostering a sense of empathy for PIC, and adding features related to assessing user satisfaction of the e-Simdatin application.